2022
DOI: 10.1097/ta.0000000000003599
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences associate with late microbiome alterations after murine surgical sepsis

Abstract: BACKGROUND: Sepsis-induced gut microbiome alterations contribute to sepsis-related morbidity and mortality. Given evidence for improved postsepsis outcomes in females compared with males, we hypothesized that female mice maintain microbiota resilience versus males. METHODS:Mixed-sex C57BL/6 mice underwent cecal ligation and puncture (CLP) with antibiotics, saline resuscitation, and daily chronic stress and were compared with naive (nonsepsis/no antibiotics) controls. For this work, the results of young (3-5 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…This group also demonstrated that after 7 days, male microbiota were dominated by Bacteroidales, while females had high abundance of Clostridiales. 13 While this study was of a model of surgical sepsis, this suggests that critical illness induces a decline in alpha-diversity and changes in beta-diversity similar to our study within 1 week 13 . Given the findings by this group, additional studies on the longer-term effects of severe trauma on the microbiome in both sexes are warranted to elucidate microbiome resilience and recovery after insult.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This group also demonstrated that after 7 days, male microbiota were dominated by Bacteroidales, while females had high abundance of Clostridiales. 13 While this study was of a model of surgical sepsis, this suggests that critical illness induces a decline in alpha-diversity and changes in beta-diversity similar to our study within 1 week 13 . Given the findings by this group, additional studies on the longer-term effects of severe trauma on the microbiome in both sexes are warranted to elucidate microbiome resilience and recovery after insult.…”
Section: Discussionmentioning
confidence: 57%
“…Unfortunately, there is a paucity of data investigating the influence of sex on the microbiome in trauma and critical illness. Efron et al 13 found that both murine males and females subjected to cecal ligation and puncture had a decline in alpha-diversity and differences in beta-diversity compared with controls after 7 days which recovered by Day 14 only in females. This group also demonstrated that after 7 days, male microbiota were dominated by Bacteroidales, while females had high abundance of Clostridiales.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we only evaluated microbiome and intestinal change in male rats; going forward, it will be important to assess sex differences between males and females. Sex has been proven to influence the microbiome, and one study had already demonstrated unique microbial composition between sexes in the setting of murine sepsis 49,50 . Finally, this study was only of rats aged 9 to 11 weeks; further studies on the potential influence of age on intestinal dysbiosis after trauma should be considered.…”
Section: Discussionmentioning
confidence: 96%
“…Sex has been proven to influence the microbiome, and one study had already demonstrated unique microbial composition between sexes in the setting of murine sepsis. 49,50 Finally, this study was only of rats aged 9 to 11 weeks; further studies on the potential influence of age on intestinal dysbiosis after trauma should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, at day 14, the microbiome of females recovers fully while that of males still differs from controls. Notably, female recovery seems age dependent; only young females are similar to controls at day 14 [ 41 ]. The authors that showed these findings have suggested that female resilience to microbiome pathogens may explain some of the sex-related differences in sepsis outcomes.…”
Section: Animal Modelsmentioning
confidence: 99%